Effect of Career Development Practices on Career Commitment and Career Success of Staff in Kachin Baptist Convention - Tawng, Malut Naw; Thaung Htet, Atar (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The objectives of the study are to examine the effect of career development practices on career commitment and to investigate the effect of career commitment on the career success of staff in the Kachin Baptist Convention, a faith-based organization. To achieve these objectives, the data collection was conducted from 144 out of 226 staff of the Kachin Baptist Convention by using structured questionnaires with a five-point Likert Scale and a simple random sampling method. After the analysis of the data, the results show that there is a positive relationship between career development practices and career commitment and also between career commitment and career success. Among career development practices, career goal progress and professional ability development play the most significant roles and also salary growth has a significant role in affecting career commitment. Among the three aspects of career commitment, career resilience and career identity have the most significant relationship with career success. Therefore, the responsible persons from Kachin Baptist Convention should focus on career goal progress and professional ability development of the staff while providing attention to support the staff in improving career resilience and identifying the career. Keywords: Triage, Guidelines and Standard of Triage, E-Triage